Análisis del movimiento turbulento en los fluidos aplicado a la caracterización de flujos cortantes libres - Tafur Ushiñahua, Otany (2018)
The purpose of this work is to study the phenomenon of turbulence at a fundamental level and as an endogenization of said knowledge, within the framework of the determination of generic equations that characterize the mechanics of unbounded shear flows, understood as one of the most common cases of the different flows that exist in nature and as industrial applications. To do this, we first began with the compilation of historical background and important works related to the phenomenon of turbulence; then an exhaustive study of the theory of turbulent flow, with the underlying knowledge involved, that is, mathematical analysis, statistical theory, fluid mechanics, etc. With the set of theoretical knowledge, it was decided to approach the problem of the characterization of the unbounded shear flows by means of the model of the conservation and transport averaged equations for the turbulent wake of a cylinder in an isothermal flow and turbulent wake of a cylinder heated. The results obtained with the considerations of incompressible flow, bidimensional, statistically stationary, with constant physical properties of the fluid and remote region of the wake; show that by approaching the problem at a first level of complexity with the averaged equations and establishing specific restrictions, the characterization of the case in question is possible and opens the way to further studies related to the methods of solving these equations.